Consumer Financial Protection Versus Catastrophic Healthcare Expenditure in Zambia - MccPowell Fombang; Richard Wamalwa Wanzala (Wiley, 2024)
ABSTRACT Background Out‐of‐pocket (OOP) expenses for healthcare are regarded as catastrophic, especially if they account for a substantial amount of a poor household's effective income. This study looks at the frequency and severity of catastrophic healthcare expenditures (CHE) to evaluate the level of monetary safeguarding provided by the present healthcare system in Zambia. Methods The study relied on the 2014 Zambia Household Health Expenditure and Utilization Survey, which was carried out in 10 different provinces. The investigated population is divided into quintiles, which divide family units into five groups, each of which represents 20% of the population. The data were analyzed using descriptive statistics, analysis of variance, and pairwise comparisons among the quintiles. Results At 5% level of significance, pairwise analyses of the average of OOP healthcare expenditures as a proportion of non‐food spending reveal that the quintiles have statistically different means. If 10% limit is employed, the concentration index CS was −0.41, whereas CO was −0.67. At a 10% limit, the adjusted headcount (HA) is 0.37, and the adjusted overshoot (OA) is 0.15%. Conclusion The frequency and severity of CHE were negligible during the study period. However, the less fortunate are more susceptible compared to the wealthy to be subjected to the occurrence and severity of CHE. Therefore, policy changes ought to emphasize the protection of the poor and vulnerable to accomplish the goal of universal healthcare (UHC). Finally, research is suggested to include equity and quality in the use of healthcare services.